ENVIRONMENTAL DECISION-MAKING SKILLS THROUGH LITERACY WORKSHEETS IN MADRASAH: AN ESD PERSPECTIVE - Ika Damayanti; Woro Sri Hastuti; Salisa Arina Haqi; Ayu Luhanarky (Nurul Jadid University, Paiton Probolinggo, East Java, 2026)
This study aimed to examine and analyze the impact of learning using environmental literacy-based worksheets on the development of environmental decision-making skills, as well as how these skills increase students' environmental awareness within the framework of Education for Sustainable Development (ESD). An experimental design was used in this study. Quantitative data were collected through improvements in students' environmental literacy using tests, observations, and questionnaires administered to 52 sixth-grade students in Indonesia, while qualitative data were obtained through interviews and classroom observations. Descriptive and correlation analyses were used to explore the relationship between the use of environmental literacy worksheets, decision-making skills, and environmental awareness. The results of the MANOVA effectiveness test showed a significance value of 0.000 < 0.05. These findings indicated that the use of environmental literacy worksheets has a significant effect on the development of environmental decision-making skills. This effect is evident in the aspects of resource use, energy conservation, and environmental problem solving. The findings imply that integrating environmental literacy-based worksheets into primary education can serve as an effective pedagogical strategy to foster sustainable decision-making competencies. Furthermore, this approach supports the practical implementation of ESD by equipping students with the skills needed to address real-world environmental challenges, thereby contributing to the development of environmentally responsible citizens.